Cocker Spaniel & Other Tools for International Understanding - Kunsthalle zu Kiel, Kiel; Ursula Blickle Stiftung, Kraichtal (Kraichtal; Kiel : Kunsthalle zu Kiel; Ursula Blickle Stiftung, 2009)
Eder, Martin ; Longhurst, Jo ; Freud, Lucian ; Parr, Martin ; Hockney, David ; Ydañez, Santiago ; Klonowska, Marta ; Valore, Lucie ; Fischl, Eric ; Emin, Tracey ; Hablik, Wenzel ; Hanson, Duane ; Pilkington, Cathie ; Wimmer, Hans ; Grünfeld, Thomas ; Kulik, Oleg ; Gormley, Anthony ; Ahtila, Eija-Liisa ; Trockel, Rosemarie ; Immendorff, Jörg ; Export, Valie ; Weibel, Peter ; Schwontkowski, Norbert ; Bonnard, Pierre ; Sarcevic, Bojan ; Bonin, Cosima von ; Rohlfs, Christian ; Klonowska, Marta ; Nagel, Peter ; Eder, Martin ; Hendricks, Jochem ; Schmidt, Erik ; Tyulkin, Vladimir ; Perrone, Diego ; Jermolaewa, Anna ; Garrin, Paul ; Baselitz, Georg ; Larsson, Annika ; Gebert, Ulrich ; Wegman, William ; Liebermann, Max
Duits
Exhibition. Cocker Spaniel & Other Tools for International Understanding (1). Exhibition. Cocker Spaniel & Other Tools for International Understanding (2). Kiel. Kraichtal-Unteröwisheim. Kunsthalle zu Kiel. Ursula Blickle Stiftung Kraichtal. 2009-09-06. 2009-10-26. 2009-10-11. 2010-01-10
boek